2020
DOI: 10.1186/s12870-019-2222-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic analyses provide insight into the volatile compounds of citrus leaves and flowers

Abstract: Background: Previous reports have mainly focused on the volatiles in citrus fruits, and there have been few reports about the volatiles in citrus leaves and flowers. However, citrus leaves and flowers are also rich in volatile compounds with unique aromas. Here, to investigate the volatiles in citrus leaves and flowers, volatile profiling was performed on leaves from 62 germplasms and flowers from 25 germplasms. Results: In total, 196 and 82 volatile compounds were identified from leaves of 62 citrus germplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Although many studies have been carried out in cereals, a wide range of non-grass studies have been performed, providing insight into the metabolic changes that occurred during domestication of a range of other species including tomato [54,98], lettuce [99], tea [100], watermelon [101], soybean [102], strawberry (Fragaria × ananassa) [103], and citrus [104]. The evaluation of the tomato metabolome was carried out at a previously unprecedented level in a large-scale multiomic study including 610 tomato accessions, extending work on a previous population assembled to gain insight into the processes of tomato domestication and improvement [105].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have been carried out in cereals, a wide range of non-grass studies have been performed, providing insight into the metabolic changes that occurred during domestication of a range of other species including tomato [54,98], lettuce [99], tea [100], watermelon [101], soybean [102], strawberry (Fragaria × ananassa) [103], and citrus [104]. The evaluation of the tomato metabolome was carried out at a previously unprecedented level in a large-scale multiomic study including 610 tomato accessions, extending work on a previous population assembled to gain insight into the processes of tomato domestication and improvement [105].…”
Section: Open Accessmentioning
confidence: 99%
“…Furthermore, quinate and chlorogenic acid levels were strongly reduced upon domestication of lettuce, probably as a consequence of the desire to reduce bitterness. Similarly, melon domestication was characterized by negative selection of cucurbitacins and flavonoids but also by elevated levels of sugars, carotenoids, and citrate:malate ratios [107], soybean domestication by negative selection of isoflavones [102], strawberry by shifts in ripening regulated metabolites [103], and citrus by negative selection on terpenoids [104]. By contrast, a pedigree and metabolite analysis in tea, which has a more complex domestication history, revealed virtually no long-term artificial directional selection for flavor-related metabolites [100].…”
Section: Open Accessmentioning
confidence: 99%
“…In a recent study, Zhang et al [22] reported the chemical composition of ten accessions of C. ichangensis. Five of ten oil samples exhibited the two aforementioned ocimenes as major components, in addition to linalyl acetate in four accessions and α-pinene in another one, whereas two of ten oil samples were dominated by sabinene, in addition to with Îł-terpinene and limonene.…”
Section: Section Papedocitrus Ichang Papeda (C Ichangensis Swingle)mentioning
confidence: 99%
“…Data concerning the chemical composition of peel and leaf oils from Citrus classified as Papeda are scarce; the literature is mainly focused on cultivated hybrids such as Yuzu [18,19]. Leaf oil composition was also reported in C. ichangensis [20][21][22]. C. hystrix is also well described in the literature [21][22][23][24], while C. macroptera leaf oil was described by Huang et al [19] and Waikedre et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…Each technological change and advancement in sequencing technology has a profound impact on transcriptome research as a means to quickly, accurately, and e ciently interpret gene-level information from medicinal plants. Because of the high-throughput, sensitivity, accuracy, and low-cost advantages of NGS, it is widely used as a technical tool to reveal more information about the genes of medicinal plants [32][33][34][35]. Currently, transcriptome studies of A. mongholicus are mainly based on NGS [28,30,36].…”
Section: Discussionmentioning
confidence: 99%